The development of anxiety The role of control in the early environment. [article]. - Chorpita, Bruce F.
Current developments in cognitive and emotion theory suggest that anxiety plays a rather central role in negative emotions. This article reviews findings in the area of anxiety and depression, helplessness, locus of control, explanatory style, animal learning, biology, parenting, attachment theory, and childhood stress and resilience to articulate a model of the environmental influences on the development of anxiety. Evidence from a variety of sources suggests that early experience with diminished control may foster a cognitive style characterized by an increased probability of interpreting or processing subsequent events as out of one's control, which may represent a psychological vulnerability for anxiety. Implications for research are discussed. -- (from the author)